2018
DOI: 10.1038/s41598-018-21604-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Preeclampsia Using Circulating Small non-coding RNA

Abstract: Preeclampsia is one of the most dangerous pregnancy complications, and the leading cause of maternal and perinatal mortality and morbidity. Although the clinical symptoms appear late, its origin is early, and hence detection is feasible already at the first trimester. In the current study, we investigated the abundance of circulating small non-coding RNAs in the plasma of pregnant women in their first trimester, seeking transcripts that best separate the preeclampsia samples from those of healthy pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 103 publications
0
36
0
Order By: Relevance
“…Another approach is to screen maternal blood for biomarkers that reflect placental function. These include miRNAs, exosomes, free DNA, proteins and short noncoding RNAs (Barchitta et al, 2017;Gaccioli et al, 2018;Rolnik et al, 2018;Tsang et al, 2017;Yoffe et al, 2018). The benefits of these screening tests in low risk populations are still not obvious, particularly as the only intervention possible at present is early delivery with obvious risk to the neonate; moreover, some reports suggest that these screening tests may actually be harmful (Monier et al, 2015).…”
Section: Abnormal Placental Development and Pregnancy Complicationsmentioning
confidence: 99%
“…Another approach is to screen maternal blood for biomarkers that reflect placental function. These include miRNAs, exosomes, free DNA, proteins and short noncoding RNAs (Barchitta et al, 2017;Gaccioli et al, 2018;Rolnik et al, 2018;Tsang et al, 2017;Yoffe et al, 2018). The benefits of these screening tests in low risk populations are still not obvious, particularly as the only intervention possible at present is early delivery with obvious risk to the neonate; moreover, some reports suggest that these screening tests may actually be harmful (Monier et al, 2015).…”
Section: Abnormal Placental Development and Pregnancy Complicationsmentioning
confidence: 99%
“…6 Serum biomarkers, uterine artery Doppler ultrasound and maternal risk have been evaluated as potential predictive tests for PE both individually and in combination but all lack sufficient sensitivity and specificity. [7][8][9][10][11] Though accuracy of the placental growth factor/soluble fms-like tyrosine kinase-1 (PlGF/sFlt-1) test is promising in triage of women at risk of early onset PE in the third trimester, its use as a first and second trimester marker appears limited. 12,13 However, a combination of maternal factors, mean arterial blood pressure, placental growth factor and uterine artery pulsatility index has shown promising results for detecting preterm PE but lacked sufficient detection rates with respect to overall PE.…”
mentioning
confidence: 99%
“…In a recent study by Timofeeva et al (2018), miR-423-5 was identified as a candidate biomarker for the early diagnosis of EOPE (19). Yoffe et al (2018) also investigated small non-coding RNAs (ncRNAs), including miRNAs, in the first trimester maternal plasma of 75 PE and control samples and identified 25 transcripts aberrantly expressed between the two groups (20). These transcripts were then used to design a model for the early prediction of PE with an average AUC value of 0.86.…”
Section: Discussionmentioning
confidence: 99%